Women admitted to forensic psychiatry in Flanders (Belgium): who are they?. Issue 2 (4th April 2022) - De Varé, Jan; de Vogel, Vivienne; de Decker, An; Tremmery, Sabine; Uzieblo, Kasia; Cappon, Leen
Abstract : Purpose: Despite the rising number of females in forensic psychiatry, research about their characteristics remains limited and is currently lacking in Belgium. Optimizing knowledge about the characteristics of these women will lead to a better understanding of this specific group. Therefore, the aim of the study was to gain insight into the characteristics of female forensic psychiatric patients in Flanders, Belgium. Design/methodology/approach: A case file study was carried out in the forensic psychiatric hospital Sint-Jan-Baptist in Zelzate, Belgium. The files of female patients admitted in the period 2006–2017 were analysed (N = 82) based on a checklist including sociodemographic, mental health care and offence-related characteristics as well as historical risk factors. Findings: The study revealed that female patients have been confronted with a large number of adverse experiences during both childhood and adulthood, were frequently diagnosed with borderline personality disorder and usually had an extensive mental health treatment history with many drop-outs. The majority of the female patients had committed violent offences towards relatives. Practical implications: These findings are similar to those of other jurisdictions and highlight the importance of a gender-responsive treatment. This kind of treatment should include trauma-informed care, gender-sensitive risk-assessment and adapted versions of dialectical behavioural therapy and schema-focussed therapy. Additionally, treatment should focus on breaking the intergenerational transmission of violence and mental health problems by targeting parenting skills. Originality/value: To the best of the authors' knowledge, this is the first study that scientifically scrutinized the detailed characteristics of female forensic psychiatric patients in Flanders, Belgium. Recommendations for gender-responsive treatment and directions for future research are discussed.